The council, senate and members of the University of Otago, New Zealand's oldest university, offer fraternal greetings and congratulations on the occasion of the 25th anniversary of our distinguished fellow institution, Universiti Teknologi Malaysia - University of Otago 4317 (Dunedin, New Zealand : University of Otago, 1997)
University of Otago;